Analisis pengaruh religiusitas terhadap preferensi busana renang pada Siswa MAN 2 Yogyakarta - Mahdiyah, Tri Ayom; Syamsudin, Syamsudin (Rafandha Press, 2023)
This research aimed at analysing and determining the effect of religiosity toward the selection of swimsuit of female students of MAN 2 Yogyakarta. The research used a causal quantitative approach, with purposive sampling method. The data were collected using likert scale model questionnaires. The data obtained were then analyzed using the prerequisite test for normality and linearity, and hypothesis test using a simple linear regression test. The results indicate that there is a significant effect of religiosity toword the selection of swimsuit of the female studens of MAN 2 Yogyakarta. The results of the hypothesis test show: (1) the religiosity of MAN 2 Yogyakarta students is included in the high level category. (2) the swimsuit selection process of female students of MAN 2 Yogyakarta is still based on the Islamic principles of wearing clothes. (3) there is a significant effect of religiosity toward the selection of swimsuit of the female students of MAN 2 Yogyakarta.